2018
DOI: 10.1002/kpm.1579
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive overload in organizational knowledge management: Case study research

Abstract: The advancements in social media are producing important effects on the way organizations manage knowledge internally, because they facilitate active participation of all employees and free knowledge sharing. This can improve the capability of companies to effectively manage tacit knowledge, which has always been considered a crucial issue in the knowledge management (KM) literature. However, the impacts of social media on KM activities have only been partially analyzed. In particular, although the benefits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…As these cognitive demands related to knowledge seeking are placed on employees cognitive processing capacity in addition to the cognitive demands related to fulfilling the demands of their work role (Elsbach & Hargadon, 2006), employees can experience knowledge overload (Savolainen, 2015). In line with our argument, research showed that employees who engaged in knowledge seeking via social media experienced cognitive overload due to the cognitive effort required to seek, select, and integrate the large amounts of available knowledge (Bolisani et al, 2018).…”
Section: Overload and Subsequent Resource Depletionsupporting
confidence: 73%
“…As these cognitive demands related to knowledge seeking are placed on employees cognitive processing capacity in addition to the cognitive demands related to fulfilling the demands of their work role (Elsbach & Hargadon, 2006), employees can experience knowledge overload (Savolainen, 2015). In line with our argument, research showed that employees who engaged in knowledge seeking via social media experienced cognitive overload due to the cognitive effort required to seek, select, and integrate the large amounts of available knowledge (Bolisani et al, 2018).…”
Section: Overload and Subsequent Resource Depletionsupporting
confidence: 73%
“…With Connect, more employees have access to information from the CoIs, and shared discussions can more easily take place, and cross‐CoI knowledge sharing is easier. However, with an ESN such as Connect comes the risk of cognitive overload if too much knowledge is made available, and this risk must be mitigated (Bolisani, Scarso, & Padova, ). The study found no data regarding mitigating actions, although Connect is continuously improved based on feedback from employees.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is a challenge to address the cognitive overload which commonly occurs when people receive too much information interfering with their short-term memory, and distracting them from their original thought process (Bolisani et al, 2018). Especially in VR environments, where multisensory information is used to increase the sense of presence.…”
Section: Challenges Of Designing Virtual Learning Environmentsmentioning
confidence: 99%